Functional near-infrared spectroscopy. - Bunce, S.C (IEEE Engineering in medicine and biology magazine)
The purpose of the this article is to describe an emerging neuroimaging technology, functional near-infrared spectroscopy (fNIRs), which has several attributes that make it possible to conduct neuroimaging studies of the cortex in clinical offices and under more realistic, ecologically valid parameters. fNIRs use near-infrared light to measure changes in the concentration of oxygenated and deoxygenated hemoglobin in the cortex. Although fNIR imaging is limited to the outer cortex, it provides neuroimaging that is safe, portable, and very affordable relative to other neuroimaging technologies. It is also relatively robust to movement artifacts and can readily be integrated with other technologies such as EEG